Analisis Penyerapan Larutan Hara Tanaman Pakchoy dan Selada Romaine pada Sistem Hidroponik Nutrient Film Technique: Nutrient Solution Absorption Analysis of Pakchoy and Romaine Lettuce Plants in Nutrient Film Technique Hydroponic System - Yohanes Bayu Suharto; Intan Kusuma Wardani (Depertemen Teknologi Pertanian Universitas Hasanuddin, 2026)
Leafy vegetables such as pakchoy and romaine lettuce have high economic value and are widely cultivated using hydroponic systems, particularly the Nutrient Film Technique (NFT). The success of this system depends on appropriate nutrient solution concentrations tailored to plant needs. This study aimed to analyze nutrient solution absorption in pakchoy and romaine lettuce grown under NFT conditions. Each crop consisted of 78 plants subjected to five ABmix nutrient treatments: control, 0%, 50%, 150%, and 200% concentrations. Observed parameters included Total Dissolved Solids (TDS), pH, nutrient absorption volume, and fresh weight growth rate. Results indicated that higher nutrient concentrations increased TDS values, while pH remained within the optimal range (6.2–7.6). Nutrient absorption rose significantly after 21 days, marking active growth. The control treatment yielded optimal absorption and plant growth performance.